ANALYSIS OF MACROSTRUCTURE AND SUPERSTRUCTURE OF CORRUPTION NEWS DISCOURSE IN NEWSPAPERS - Hari Bakti Mardikantoro; Muhammad Badrus Siroj; Esti Sudi Utami (Universitas Negeri Makassar, 2020)
This study aims to determine the construction of news texts in newspapers, especially in the dimensions of macrostructure and superstructure. This study used a descriptive qualitative approach with the analysis of Teun van Dijk's critical discourse, specifically the dimensions of the text. The results showed that in reporting corruption cases in Suara Merdeka, Republika, Kompas, and Jawa Pos newspapers, journalists constructed the news cases by focusing on news themes about ongoing corruption. Meanwhile, in the superstructure dimension, a number of news scheme categories are formulated to build a story, which is a summary, which is marked by two elements namely the title and lead and story, namely the overall news content from introduction to the end.